DETECTION OF SEROTYPES AND KNOCKDOWN-RESISTANCE MUTATIONS IN DENGUE AND OTHER FLAVIVIRUS SAMPLES COLLECTED FROM MENGARE ISLAND, INDONESIA - Dwiyanti, Tasya Amalia; Sucipto, Teguh Hari; Suhandarini, Khoirunnisa; Fathiarachman, Azizia Kanya; Nastiti, Helena Putri; Putri, Anika Rahma; Fauziyah, Shifa; Widiyanti, Prihartini; Hariyono, Hariyono; Rehman, Saifur (Folia Medica Indonesiana, 2025)
Dengue fever, caused by the dengue virus (DENV), poses a significant public health challenge, particularly in tropical regions. This study aimed to detect flavivirus presence, DENV serotypes, and knockdown-resistance (kdr) mutations in mosquito samples collected from Mengare Island, Gresik, Indonesia. A cross-sectional experimental design was employed, utilizing reverse transcription polymerase chain reaction (RT-PCR) for flavivirus detection and serotyping, as well as for identifying kdr mutations. Ribonucleic acid (RNA) extraction was performed using the Quick-RNA™ Miniprep Plus Kit (Zymo Research, Irvine, CA, USA), followed by RT-PCR with specific primers for DENV serotypes 1–4 and kdr mutations (V1016G and F1534C). Six adult female Aedes albopictus mosquitoes were analyzed in this study. The results revealed no evidence of flavivirus infection or DENV serotypes in the mosquito samples, as no complementary deoxyribonucleic acid (cDNA) bands corresponding to expected base pair sizes were observed on the agarose gels. Similarly, the analysis of kdr mutations showed that all samples were homozygous wildtype, with no mutations detected at the V1016G or F1534C loci. In conclusion, these findings suggest the absence of active dengue virus transmission or notable insecticide resistance in the studied mosquito population from Mengare Island. This study highlights the importance of continuous monitoring of flavivirus presence and resistance mutations. The variability in kdr mutation frequencies across regions underscores the need for sustained surveillance and effective control measures to mitigate potential outbreaks in high-risk areas such as Mengare Island.